2018
DOI: 10.1111/nep.13458
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on acute kidney injury strategy in China

Abstract: Acute kidney injury (AKI) has imposed a heavy disease burden in China, with substantial underdiagnosis and undertreatment. The incidence, cause and outcome of patients with AKI vary according to different geographic regions and economic development status; therefore, regional improvement strategies are needed. Defining the etiology of AKI is critical in making the proper therapeutic regimen, and a multidisciplinary cooperative AKI team is essential in order to establish the early diagnosis and proper managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…The incidence of S-AKI in LI's paper was only 6.4% 16 . The current literature reported incidence of S-AKI is from 39.4-60.7% in ICU 21,22 , which is consistent with our nding (48%).…”
Section: Discussionsupporting
confidence: 93%
“…The incidence of S-AKI in LI's paper was only 6.4% 16 . The current literature reported incidence of S-AKI is from 39.4-60.7% in ICU 21,22 , which is consistent with our nding (48%).…”
Section: Discussionsupporting
confidence: 93%
“… 1–5 The current literature reported incidence of S-AKI is from 39.4% to 60.7% in ICU, which is consistent with our finding (48%). 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] The current literature reported incidence of S-AKI is from 39.4% to 60.7% in ICU, which is consistent with our finding (48%). 22,23 According to the nationwide survey regarding AKI across Mainland China, 72% of AKI episodes occurred in the non-ICU setting, which reminds us that the occurrence of AKI outside the ICU requires more attention. 17 Our study showed that certain demographic characteristics, including advanced age, male and the presence of comorbidities such as hypertension, CKD and liver cirrhosis, and severity of the diseases as assessed by requirements for ICU admission and shock status were significantly associated with the incidence of AKI.…”
Section: S-aki Patients In Traditional Chinesementioning
confidence: 99%
“…The higher incidence of AKI in our study might be due to frequent creatinine measurements. In this study, 88% of patients had serum creatinine levels measured twice or more, which is much more frequent than the repeated detection rate of 25.3% in China and 63.2-67.6% in developed countries [29]. Therefore, our detection rate is closer to the actual incidence of AKI in older adults in the real world.…”
Section: Discussionmentioning
confidence: 46%